(untitled) (Scientific journal of the Fergana State University, 2023)
This article touches upon the morphological ways of eхpressing the verbalizers of the conceptual macrosemantics of “intensification” established for the first time in Modern English, Uzbek and Russian, which allowed the author to reveal the isomorphic and allomorphic features of the verbalizers and the factors preconditioning the latter.